(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Introduction: The Candida species are responsible for various clinical infections ranging from mucocutaneous infection to life threatening invasive diseases. The treatment of choice is the use of azoles, such as fluconazole (FLC). The mutations in ERG11 and amino acid substitutions in the target enzyme ERG11 leads to changes in the tertiary structure of enzyme and subsequently alter the abilities of azole antifungals. Aim and Objective: To determine the Antifungal Susceptibility Pattern of Candida albicans and the Molecular Characterization of ERG11 gene of Fluconazole Resistant Candida albicans isolates at a Tertiary Care Centre. Material and Methods: This was a cross sectional study carried out in the Department of Microbiology at Rama Medical College Hospital and Research Centre, Mandhana ,Kanpur for a period of 1 year i.e, August 2021 to August 2022. A total of 70 consecutive Candida species were isolated from 823 clinical specimens. Growth on Sabouraud dextrose agar were evaluated for colony appearance, microscopic examination, Gram staining, germ tube test and urea hydrolysis test. Further, they were processed for Candida speciation on CHROMagar. Antifungal susceptibility testing was performed as recommended by Clinical and Laboratory Standards Institute (CLSI) guidelines 2021. The DNA isolation was done using the Qiagen DNA extraction kit followed by the PCR for the molecular detection of ERG11 gene. Results: Out of the total 70 Candida isolates, Candida albicans 29 (41.4%) was the most common species. Among the non-albicans Candida species, Candida tropicalis 20 (28.5%) was the predominant isolate followed by Candida glabrata 17 (24.2%) and least by C. krusie 4 (5.7%). The ratio of Males 18 (62%) was more as compared to that of the Females 11( 37.9%) with the maximum age of 31-40 years and least in the age group above 61 years of age. The number of isolates was maximum in the urine sample. The ERG11 gene was detected in all the fluconazole resistant 4 (13.7 %) strain of candida albicans. Conclusion: In the current study nearly 4(13.7%) of the Candida albicans indicates a reduced sensitivity to the effects of azole drugs. Therefore, understanding how all Candida spp. display resistance to fluconazole is crucial if we are to maintain the efficacy of this essential antifungal treatment.